(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
Starting from an acknowledgement of the inescapability of the question of the analytical-methodological space for the study of power, this paper presents a reflection upon an analytical-methodological principle that has increasingly informed the terrain of social sciences, namely methodological individualism, as it features in neoclassical economics. Contextually, by drawing upon the author’s research experience, the paper offers some reflections on the dialogue between theory and the field. It takes an analytical approach informed by methodological holism and which adopts the lens of critical political economy to interrogate the unfolding of specific social power dynamics. In so doing, the paper dwells upon the importance recognized, within such an approach, of individual life stories.